Analisa Perbandingan Performansi AC SPLIT Konvensional Dengan AC SPLIT Tenaga Surya - Yudhy Kurniawan (Politeknik Negeri Padang, 2021)
Currently, the world's energi needs are still dominated by depleting fossil fuels, where the largest consumption produced from these fossils is electrical energi. For tropical country conditions, on average, every house and in city buildings use split AC as a tool to condition the room so that it feels comfortable for its residents. Where about 60% utilize electrical energi. In this study, split AC uses solar power as an alternative to electrical energi by using a solar photovoltage (PV) system as a medium for absorbing solar radiation to be converted into electrical energi in split AC. The goal is that the use of solar radiation is able to reduce the use of electricity from PLN, which so far requires a large amount of money. The research method begins by making a model of a device that is modified by an electric panel on a split AC connected to an inverter to convert DC to AC current from the PV cell. From the use of solar cells as electrical energi then the test results are compared with conventional split AC. The results obtained from the conventional split AC test can be seen that the efficiency is 85% while the solar-powered split AC has an efficiency of 73%, but for the use of electrical power that operates for 2 hours on a solar-powered split AC, it is more efficient with a power of 376 Wh per day.